Answer:
We can write this equation in slope-intercept form
y
=
m
x
+
b
where
m
is the slope and
b
is the
y
-intercept.
We know
m
=
−
4
and
b
=
6
, so we can insert these into the equation to get
y
=
−
4
x
+
6
Hope this helps!
Answer:
C
Step-by-step explanation:
Given
(3x + 7)(2x - 6)
Each term in the second factor is multiplied by each term in the first factor, that is
3x(2x - 6) + 7(2x - 6) ← distribute both parenthesis
= 6x² - 18x + 14x - 42 ← collect like terms
= 6x² - 4x - 42 → C
Answer:
one is smaller then the other i think thats it
Step-by-step explanation:
Answer: 27
Step-by-step explanation:
supposed to ad 6 everytime
Answer:
A
Step-by-step explanation:
A